Analisis Ungkapan Sumimasen dalam Anime Bungou Stray Dogs Karya Kafka Asagiri - Syalsabilla Rahmah; Damai Yani (Universitas Negeri Padang, 2021)
Japanese has the concept of apologizing, because in Japanese there are levels of language. There are also various apologies in Japanese, one of which is the sumimasen expression. In learning Japanese, especially in basic learning, sumimasen expressions are often found. This is because the expression sumimasen means formally apologizing or is included in learning aisatsu which is basic learning in Japanese. The purpose of this research was carried out because the expression sumimasen does not have a meaning as an expression of apologizing only, but can be used in different situations according to the context. This study used a qualitative descriptive method using a pragmatic approach. The technique used in this research is note tapping technique, in which the researcher himself acts as an observer in processing the data contained in the data source. This research focuses on the meaning of the sumimasen expression in the anime Bungou Sray Dogs by Kafka Asagiri. The results of this study are that although the expression sumimasen has 4 different meanings according to the context and situation of the speech, the meaning that is widely available and used is the meaning of apologizing. From these results, it can be seen that in Japanese the meaning of the expression sumimasen is used more as apologizing than the meaning of expressing gratitude, asking for help, or attracting attention or expressions of excuse.